Direct and legacy effects of genotypic diversity on population performance of Hydrocotyle vulgaris. (November 2022) - Begum, Ghazala; Gao, Jun-Qin; Song, Ming-Hua; Xue, Wei; Yu, Fei-Hai
Highlights: Genetic diversity plays important roles in population dynamics and productivity. Both direct and soil legacy effects of genetic diversity on populations were tested. Genetic diversity directly affected population productivity and size of Hydrocotyle vulgaris . Genetic diversity had soil legacy effects on population productivity and size of H. vulgaris . Abstract: Genetic diversity can have important ecological consequences on population dynamics and ecosystem functions and processes. While the direct effect of genetic diversity on population performance has been widely documented, its soil legacy effect has received little attention. To assess both the direct and soil legacy effects of genetic diversity on population performance, we conducted a plant-soil feedback experiment with 12 genotypes of a clonal plant Hydrocotyle vulgaris . We first conditioned soils (conditioning phase) by growing populations of H. vulgaris consisting of 1, 2, 4 and 8 genotypes in the soils and then tested the soils (test phase) by growing populations consisting of all 12 genotypes in sterilized bulk soils inoculated with each of the conditioned soils at a volume ratio of 10%. At the end of the conditioning phase, both biomass and the number of ramets of the populations of H. vulgaris first decreased and then increased with increasing genotypic diversity, indicating a direct effect of genetic diversity on population performance. At the end of the test phase, both biomass and number of ramets were significantly higher when the populations were grown in the soils conditioned by the populations consisting of 1 and 2 genotypes than when they were grown in the soils conditioned by the populations consisting of 4 and 8 genotypes, suggesting a soil legacy effect. Therefore, genetic diversity can have both a direct and a soil legacy effect on population productivity and size of H. vulgaris . These results highlight the importance of intraspecific differences on population performance and suggest that soil legacy effects should also be considered to fully understand the role of genetic diversity.